Effect of Cyclic Stresses below the Endurance Limit on the Fatigue Life of 40Cr Steel - Zhao, L.H.; Feng, J.Z.; Zheng, S.L. (Проблемы прочности, 2018)
The effect of cyclic stresses below the endurance limit on the fatigue life of 40Cr medium-strength carbon steel is studied. Conventional constant-amplitude cyclic tests and specially designed variableamplitude ones are conducted under torsional loading at the stress ratio R = 0.1. The results show that the strengthening effect of cyclic stresses below the endurance limit can be reached if they are applied prior to the exceeding ones. Moreover, the stress amplitude, number of cycles and load sequence are found to be the three major strengthening effect-controlling factors. Изучено влияние циклических напряжений ниже предела выносливости на усталостную долговечность углеродистой стали средней прочности 40Cr. Выполнены стандартные циклические испытания с постоянной амплитудой и специально разработанное испытание с переменной амплитудой при крутящем усилии и коэффициенте асимметрии R = 0,1. Показано, что эффект упрочнения от циклических напряжений ниже предела выносливости достигается при их приложении до напряжений, превышающих этот предел. Установлено, что амплитуда напряжений, число циклов и схема нагружения являются тремя основными факторами, контролирующими эффект упрочнения.